PEMANFAATAN MICROSOFT TEAMS DENGAN TEKNIK EVALUASI DIRI UNTUK MENINGKATKAN HASIL BELAJAR - I Made Nuryata (Direktorat Guru dan Tenaga Kependidikan Pendidikan Menengah dan Pendidikan Khusus, 2021)
This research aims (1) Improving Automotive Engineering Image learning outcomes of grade X TKRO2 students of SMKN 3 Singaraja, Academic Year 2020/2021 through the utilization of Microsoft Teams with self-evaluation techniques, (2) Knowing the responses of grade X TKRO2 students of SMKN 3 Singaraja, Academic Year 2020/2021 towards the utilization of Microsoft Teams with self-evaluation techniques in Automotive Engineering Image subjects. The objects of this research were: (1) learning outcomes in the aspects of knowledge, attitudes and skills, (2) students’ responses to the utilization of Microsoft Teams with self-evaluation techniques. The data collection techniques used were written tests, performance tests, observations and questionnaires. In the first cycle, the average of students’ learning outcomes in the knowledge aspect was 66.25, the skills aspect was 75.25 and the attitude aspect was in Good category. In the second cycle, students with subjects understanding level less than 70% were given guidance through personal chat on Microsoft Teams. The average of learning outcomes in the knowledge aspect was 76.39 increased 15.3%, the skills aspect was 76.81 increased 2,1% and the attitude aspect was in Good category. Students’ responses to the utilization of Microsoft Teams with self- evaluation technique was categorized very good 39%, good 50% and quite good 11%. The conclusions of this research are: (1) The utilization of Microsoft Teams with self-evaluation techniques can improve learning outcomes of grade X TKRO2 students of SMKN 3 Singaraja, Academic Year 2020/2021. (2) The responses of grade X TKRO2 students to the utilization of Microsoft Teams with self-evaluation techniques in learning Automotive Engineering Image, Academic Year 2020/2021 is categorized Good.